Modeling of Interaction between Sole of Ankle-Foot Orthosis, Soft Tissue, Bones, Cartilage and Tendons in Steppage Gait Disorder through FEM Method for Tension Reduction in Patient Foot - N. jamshidi; H. Hanife; M. Rostami; S. Najarian (Afarand Scholarly Publishing Institute, 2012)
Introduction: In this study, a three dimensional finite element model of human walking with ankle foot orthosis has been made in accordance with the kinematics data of neuropathic patients with drop foot in order to optimize the role of orthosis through minimizing stress on patientchr('39')s sole. Methodes & Materials: The required kinetics data for the model were captured through force plate and then analyzed by BioWare software. In this model, the tension in soft tissue and bones during stance phase of gait was calculated. Then the tension variations on joints have been assessed by considering the role of ankle-foot orthosis. Unlike previous researches, the role of orthosis on bone and soft tissue tension has been modeled dynamically and continually. In addition, the contact between the orthosis and sole has been considered in this model. Result: The tension reduction in sole can improve the role of foot orthosis during abnormal walking and the most optimized sole of orthosis in accordance with kinetics data of each patient can be designed.